Keep your friends close [large type] - Berry, Lucinda (Center Point Large Print, 2024)
"When Kiersten McCann, president of the West Hollywood Moms' Club, turns up dead in her own pool, it quickly becomes clear this wasn't an accident. And the party guests -- all members of the exclusive club -- are now key suspects in her murder. Accusations fly, and three mothers find themselves at the center of the investigation. Whitney, Brooke, and Jade all have heavy secrets to bear . . . and possible motives for their friend's murder. But as the police look closer, more secrets, betrayals, and sinister plots are revealed than the women could ever imagine. With everything at stake, deceit threatens to shatter their illusions of the perfect life. West Hollywood will never be the same."--